Seals : making and marking connections across the Medieval world - Bedos-Rezak, Brigitte (Medieval globe, 2018)
"By placing medieval sealing practices in a global and comparative perspective, the essays gathered in this volume challenge the traditional understanding of seals as tools of closure and validation in use since the dawn of civilization. Far from being a universal technique, sealing is revealed as a flexible idiom, selectively deployed to mediate entangled identities: the introduction of Buddhism in early medieval China; the Islamization of Sasanian and Byzantine cultures; the balancing of Christian orthodoxy against classical and Muslim science; the development of civic consciousness in Byzantium; the efforts of tradesmen to brand merchandise for export; and the advancement of diplomacy from northern Europe to Indonesia. This examination of documentary seals, archaeologically recovered seal dies, and commercial and conceptual seals from cultures across the medieval world shows how skillful manipulation of their iconography, inscriptions, technology, and metaphorical meanings disseminated information, negotiated influences, asserted hegemony, and forged connections."--Bloomsbury Publishing.